Diagnostic approach for precancerous and early invasive cancerous lesions of the uterine cervix - Grubišić, Goran, liječnik (Array, 2009)
Abstract: Invasive cervical cancer is second most common female cancer worldwide with about 493 000 new cases per year. About 273 000 women die from cervical cancer each year, 85% of which take place in developing countries. Cervical cancer has a slow progress, from pre-invasive cervical intraepithelial neoplasia (CIN) to invasive phases, meaning that the disease can be diagnosed while in the phase of pre-invasive lesion, and treated successfully thanks to the regular screening of asymptomatic women (the Pap smear). The authors review new possibilities of early detection of cervical cancer with emphasis on colposcopy. The role of colposcopy is discussed among possibilities of early diagnosis. The authors discuss additional diagnostic procedures for preinvasive lesions of the uterine cervix like DNA cytometry, (flow cytometry). This method can point to dysplasia which can progress to severe stages, such as HSIL (High grade Squamous Intraepithelial Lesion). If the level of chromosomal disturbance is higher (aneuploidy), it is more probable that HSIL will develop. Laser screening of cells extracted with modern cytologic screening LBC (Liquid Base Cytology) enables us to automatically measure ploidy (chromosome regularity, or irregularity) and PCR provides analysis of HPV types. These methods are recommended for a routine check-up of borderline cervical lesions in order to anticipate ones likely to regress or progress